Closure of Secundum Atrial Septal Defects by Using the Occlutech Occluder Devices in More Than 1300 Patients: The IRFACODE Project: A Retrospective Case Series. Issue 4 (31st March 2016) - Haas, Nikolaus A.; Soetemann, Dagmar B.; Ates, Ismail; Baspinar, Osman; Ditkivskyy, Igor; Duke, Christopher; Godart, Francois; Lorber, Avraham; Oliveira, Edmundo; Onorato, Eustaquio; Pac, Feyza; Promphan, Worakan; et al.
Abstract : Background: The Occlutech Figulla ASD device series (OFSO) shows an improved device design for interventional ASD closure, larger follow‐up series are missing. Methods: We retrospectively reviewed the feasibility, safety, implantation properties, results, and follow‐up of ASD closure using Occlutech devices over a 5 year period by establishing a multi‐institutional collaborative result registry with 16 contributing centers from 11 countries (IRFACODE). Results: In 1315 patients of all age groups (female 66.9%), successful (98%) ASD closure was performed (mean age 28.9 years, weight 52 kg, height 148.6 cm). Of the defects, 47.9% showed no or only a deficient aortic rim; in 11.9%, there was more than one defect; a septum aneurysm was present in 21.5%; and the mean implanted device size was 20.5 mm. Immediate closure was achieved in 78.6%, at discharge in 83.1%, and 96.4% and 97.3% at 6 and 12 months follow‐up, respectively. During a mean follow‐up of 2.7 years (in total 3597 patient years), significant complications were minimal (total = 8, <1%) with secondary device embolizations in five and AV‐blocks in three patients. No erosion or death was reported. Conclusion: ASD closure using OFSO is feasible in a large variety of patients, safe with only a minimal risk of severe side effects and especially without any aortic erosions despite a large percentage of large and complicated defects. © 2016 Wiley Periodicals, Inc.